Factors affecting microcredit demand among woman small medium entrepreneur : a case study of Amanah Ikhtiar Malaysia Segamat / Nurazila Mastuki - Mastuki, Nurazila (Faculty of Business Management, 2015)
The Malaysia government had been using the microfinance as one of tools to achieve its mission to reduce poverty and achieve a high-income status by 2020. Three (3) steps taken by Bank Negara Malaysia (BNM) to create a sustainable microfinance industry: Encourage financial institutions to provide microfinance. Design right product to meet the needs of micro enterprises and create widespread awareness on the availability and benefits of microfinance. However, it was reported that the effectiveness of promotional efforts to raise public awareness of the availability of microfinance is an issue to be looked into. As such, this study was to examine the factors affect microcredit demand among woman entrepreneur in Amanah Ikhtiar Malaysia Segamat. By determining the current factors of microcredit demand in Segamat, the study zoomed in and focused on studying the determinants that influencing of microcredit demands in AIM Segamat. The contribution made by this study is to improve understanding and awareness level of micro enterprise that people will know the availability of microfinance that can assist them to start their micro business.